Understanding the scabbling of concrete using microwave energy - Buttress, A.J.; Jones, D.A.; Dodds, Chris; Dimitrakis, Georgios; Dawson, Andrew; Kingman, S.W. (Elsevier, 2015)
This paper reports on the use of microwave energy to scabble concrete. While the technique is not new, little information exists relating to the controllability of the process, the effect of different types of concrete and the performance and durability of the scabbled concrete post treatment. Concrete blocks supplied by the UK Sellafield nuclear site were treated with microwave energy using a 15kW system, operating at 2.45GHz. The effect of aggregate type (Whinstone, Gravel and Limestone); standoff distance; and effect of surface coating were studied to determine their influence on the systems performance, in terms of mass and area removal rates. Complimentary modelling studies were undertaken relating the power density of the microwave energy to observed scabbling profile. Mass and area removal rates averaged 11.3gs-1 and 3cms-1 respectively on treating large areas to a depth of 25mm. The process was shown to not adversely affect structural properties of the specimens after treatment.